1997
DOI: 10.3171/foc.1997.2.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow as a predictor of outcome following traumatic brain injury

Abstract: As part of a prospective study of the cerebrovascular effects of head injury, 54 moderate and severely injured patients underwent 184 133Xe-cerebral blood flow (CBF) studies to determine the relationship between the period of maximum blood flow and outcome. The lowest blood flows were observed on the day of injury (Day 0) and the highest CBFs were documented on postinjury Days 1 to 5. Patients were divided into three groups based on CBF values obtained during this period of maximum flow: Group 1 (seven patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 40 publications
4
52
0
3
Order By: Relevance
“…Marked decrease in CBV and CBF has been found 3 to 4 h after injury in the rat model of closed head injury (Prat et al, 1997;Thomale et al, 2002). Local CBF has been found to decrease 15 mins after injury and remain decreased up to 4 h in lateral fluid percussion rat models (Ginsberg et al, 1997) and similar patter of CBF has been found in humans Kelly et al, 1996Kelly et al, , 1997. Interestingly, in experimental models transient hypoperfusion has also been detected in the contralateral hemisphere (Pasco et al, 2007).…”
Section: Introductionmentioning
confidence: 53%
“…Marked decrease in CBV and CBF has been found 3 to 4 h after injury in the rat model of closed head injury (Prat et al, 1997;Thomale et al, 2002). Local CBF has been found to decrease 15 mins after injury and remain decreased up to 4 h in lateral fluid percussion rat models (Ginsberg et al, 1997) and similar patter of CBF has been found in humans Kelly et al, 1996Kelly et al, , 1997. Interestingly, in experimental models transient hypoperfusion has also been detected in the contralateral hemisphere (Pasco et al, 2007).…”
Section: Introductionmentioning
confidence: 53%
“…9 Rodent and human studies have found that the CBF is decreased in the first 24 hours after TBI, 10,11 followed by a period of increased CBF. 12,13 The subacute phase is less studied, but CBF is reportedly decreased. 14 Relatively few studies have been performed in children with TBI.…”
Section: Traumatic Brain Injury (Tbi)mentioning
confidence: 99%
“…increased perfusion in the tissue capillary bed and vasculature during the next 3 days), and vasospasm that invokes a fall in the CBF that lasts for the next two weeks. Particularly, decreased CBF acutely after impact has been documented (Kelly et al, 1996;Kelly et al, 1997;Martin et al, 1997). Long term deviations from the normal CBF level have been depicted, and even patients with symptomatic mild traumatic brain injury but without any other abnormal MRI findings have shown persistent regional hypoperfusion (Bonne et al, 2003).…”
Section: From Morphology To Function -Hemodynamic Alterations After Tbimentioning
confidence: 99%